Treatment of poultry litter does not improve performance or carcass lesions in broilers - de Oliveira, Maria C; Gonçalves Bruno N; Pádua Gracielle T; da Silva Virgínia G; da Silva, Denis V; Freitas, Arthur IM (Revista Colombiana de Ciencias Pecuarias, 2015)
Background: broilers spend most of their lives in contact with litter; litter quality can affect their health and performance. Objective: the effects of litter treatment on performance and carcass lesions were evaluated in five consecutive flocks with 640 male broilers each. Methods: a completely randomized model was used comprising eight treatments and four replicates. The treatments included (1) untreated litter, (2) litter subjected to in-house composting, (3) litter treated (LT) with aluminum sulfate, (4) LT with gypsum, (5) LT with quicklime, (6) LT with dolomitic limestone, (7) LT with zeolite, and (8) LT with charcoal. Chopped elephant-grass hay was used as poultry litter in all flocks. Results: none of the litter treatments were found to influence the performance and carcass lesions of the male broilers in all five flocks. Furthermore, poultry litter treatments were not economically viable. Conclusion: poultry litter treatments did not affect the performance and scores of carcass lesions of male broilers, but increased the cost of poultry production.